Pattern cutting the architecture of fashion - Parish, Pat (London Bloomsbury Visual Arts, 2017)
"Pattern Cutting: The Architecture of Fashion demystifies the pattern cutting process and clearly demonstrates pattern fundamentals, enabling you to construct in both 2D and 3D, and quickly get to grips with basic blocks, shape, sleeves, collars, trousers, pockets and finishes"--Provided by publisher.
Keywords: Dressmaking -- Pattern design; Pattern cutting of clothing